Wound healing activity of Ullucus tuberosus, an Andean tuber crop (2017)
ABSTRACT: This study was designed to investigate the wound healing activity of aqueous extracts of Ullucus tuberosus (U. tuberosus) using in vitro models. Lyophilized pulp and acetone extracts of U. tuberosus were produced using ultrasound extraction. The capacity for collagenase activation was evaluated using fluorescence detection of the enzymatic activity. Then, the influence of U. tuberosus extracts on cell proliferation, cell migration and synthesis of the extracellular matrix (ECM) proteins, metalloproteinase (MMP-1) and pro-collagen was analyzed using human dermal fibroblasts in culture. An increase in collagenase activity of 12% supports the utility of U. tuberosus as an agent for scar treatment. In addition, the extracts showed an increase in the proliferation and migration of human dermal fibroblasts and the production of pro-collagen and MMP-1 after treatment with U. tuberosus extracts. The increase in proliferation, migration and pro-collagen levels positively influenced the regeneration of scarless tissue during the proliferation phase, whereas the increase in MMP-1 may have favored the wound healing process during the remodeling and cellular differentiation phases. The results of this study show for first time that U. tuberosus is a promising candidate to support scarless tissue regeneration.